Performance of Ovarian Response Prediction Index As Predictor of Ovarian Response - Dagvadorj, Bolormaa; Erdenebileg, Nasantogtokh; Davaasuren, Enkhmaa; Shirchinjav, Altantuya; Jamsranjav, Enkhtsetseg; Dagvadorj, Otgontsetseg (Central Asian Journal of Medical Sciences, 2022)
Objective: We aimed to evaluate potential predictors of response to controlled ovarian stimulation (COS), including follicle stimulating hormone (FSH), Estradiol, antral follicle count (AFC), and ovarian response prediction index (ORPI). Methods: In this prospective, single center study, we recruited 55 infertile women underwent the first cycle of in vitro fertilization/ intracytoplasmic injection/intrauterine insemination (IVF/ICSI/IUI). We measured serum FSH and anti-mullerian hormone (AMH) level by ELISA and evaluated AFC. In accordance with formula, AMH x AFC / patient's age, ORPI was calculated. Results: The study participants are aged between 25 to 48 in infertility women. The mean age of the participants are 34.5 ± 5.5. The hormonal predictors, as well as ovarian response, are presented in Table 2. Predict ovarian hypo response by E2 and ORPI. Multivariable models improved the predictive accuracy for hypo-response (AUC > 0.6). With regard to the hyper-response, ORPI, E2 and AFC showed good predictors. In the multivariable model, the ORPI, E2 and AFC presented the best predictive accuracy, with an AUC 0.81, a sensitivity of 87 %, and a specificity of 67 %. Conclusion: ORPIndex is predicting the hyper-response more accurately than the ovarian hypo- response in infertility women. Participant’s ovarian reserve biomarkers (AFC and E level) was significantly increased predictive accuracy.